A Comparative Study of Workplace Bullying Among Public and Private Employees in Europe. Issue 6 (June 2015) - Ariza-Montes, Antonio; Leal-Rodríguez, Antonio L.; Leal-Millán, Antonio G.
Abstract : Objectives: Workplace bullying emerges from a set of individual, organizational, and contextual factors. The purpose of this article is hence to identify the influence of these factors among public and private employees. Methods: The study is carried out as a statistical–empirical cross-sectional study. The database used was obtained from the 5th European Working Conditions Survey 2010. Results: The results reveal a common core with respect to the factors that determine workplace bullying. Despite this common base that integrates both models, the distinctive features of the harassed employee within the public sector deal with age, full-time work, the greater nighttime associated with certain public service professions, and a lower level of motivation. Conclusions: The present work summarizes a set of implications and proposes that, under normal conditions, workplace bullying could be reduced if job demands are limited and job resources are increased.